Past, present, and future perspectives of heparins in clinical settings and the role of impaired renal function - Harenberg, Job (International journal of cardiology, 2016)
Heparin, whose discovery goes back one hundred years, was first detected as a thromboplastin from liver tissue, and its anticoagulant action was only identified later. The procoagulant action of heparin, which was later characterized as an immunologic reaction by binding to platelet-factor IV, presenting as heparin-induced thrombocytopenia, remains as a side effect. For more than 60 years heparin has been the immediate anticoagulant of choice in many clinical indications. Further development of heparins resulted in the production of low-molecular weight heparins and Fondaparinux, which substituted heparin for many indications and has received many more new indications, including administration for non-anticoagulant purposes. This development is still ongoing and has resulted in more than 300 registered clinical trials at the end of 2015. All types of heparins are still investigated in patients with impairment of renal function to improve the safety of treatment. New therapeutic strategies for the prevention and treatment of thromboembolism, as well as of the non-anticoagulant actions of natural and modified types of heparins, are studied intensively. The clinical study designs include treatment with vitamin-K and non-vitamin K oral anticoagulants. Consequently, heparins, low-molecular weight heparins and Fondaparinux play an important role in the human health care system.
Gesehen am 26.08.2019